Associations between nutrient intake and osteoarthritis based on NHANES 1999 to 2018 cross sectional study - Xiaofeng Lv; Xinmin Deng; Rui Lai; Shanshan Liu; Zihao Zou; Xuechun Dai; Yalan Luo; Jian Luo; Ying Li (Scientific Reports)
Abstract The relationship between nutrient intake and osteoarthritis (OA) remains unclear. This study utilized data from the National Health and Nutrition Examination Survey (NHANES) in a multi-cycle retrospective cohort study to explore the associations between the intake of six nutrients—carbohydrates, dietary fiber, protein, fat, folate, niacin and OA. This study performed a cross-sectional analysis using NHANES data from 1999 to 2018 to investigate the relationship between the intake of six nutrients and OA. Univariate and multivariate weighted logistic regression models, along with restricted cubic splines (RCS), were applied to assess the associations between nutrient intake and OA. A total of 32,484 participants were included in the study, of whom 1864 were diagnosed with OA, resulting in a prevalence rate of 5.74%. Multivariate weighted logistic regression consistently demonstrated that dietary fiber, folic acid, and nicotinic acid intake were negatively associated with the presence of OA, while protein intake exhibited a J-shaped relationship with OA, and carbohydrate or fat intake showed no significant association with OA. Compared with participants in the lowest quartile (Q1), those in the highest quartile (Q4) of dietary fiber, folic acid, and nicotinic acid intake had 27%, 28%, and 33% lower odds of having OA, respectively, after adjusting for potential confounding factors. RCS analysis revealed that dietary fiber and nicotinic acid intake had a nonlinear relationship with the presence of OA, folic acid intake had a linear relationship with OA, and protein intake followed a J-shaped curve with OA. These results suggest that higher intake of dietary fiber, folic acid, and nicotinic acid is associated with a reduced likelihood of OA, while protein intake follows a J-shaped curve, with moderate intake offering the greatest protection. These findings highlight the importance of balancing protein intake and optimizing the consumption of other nutrients for the prevention and management of OA. Further research is needed to confirm these findings and clarify the underlying mechanisms.